Perception of environmental landscape and its Potential, province of Huamalies - Meza Arquiñigo, Carlos (2010)
The study is aimed to investigate the benefits that different altitude levels of the landscapes in the province of Huamalíes, with the purpose of zoning areas. In this regard we propose the next target. Determine their qualities and potential of natural resources in different altitudinal zones, through the use and interpretation of satellite imagery, Geographic Information Systems and knowledge I insist the landscape, with the aim of proposing some of the proposed legislation geographical space for its development. Were identified five natural regions: Janca, Puna, Suni, Quechua and Rupa Rupa, which are between 680 and 4950 msnmm, the presence of Occidentatal and Eastern Cordillera of the Andes, the watersheds of the rivers Marañón Monzon and are potentially make mineral and energy resources, where mining has been exploited in the form artesanal.y exploitation of water resources is reduced